Digital Transformation of Kitabah Learning in Indonesia: A Sinta2-Indexed Journal Analysis - Dewi, Azzaria Mida Mustika; Shodiq, Muhammad Jafar; Sani, Nurhikmah; Sofa, ⁠Faizmailiatus (Al-Arabi: Jurnal Bahasa Arab dan Pengajarannya = Al-Arabi: Journal of Teaching Arabic as a Foreign Language, 2024)
One good way of expressing your thoughts and feelings is by writing. The existence of maharah kitabah learning can help students express their thoughts and feelings. In this digital era, there are many ways to practice writing skills. In this case, it can be seen from the development of maharah kitabah learning. The purpose of this study is to determine the digital development of maharah kitabah learning in the Sinta 2 journal for 2020-2022. The method used in this study is a literature review with a qualitative approach. Literature review will provide an overview of the development of a particular topic. Literature review will allow a researcher to identify a theory or method, develop a theory or method, identify gaps that occur between a theory and relevance in the field / to a research result. The results obtained from this study are, because this research is limited to accredited journals of the sinata 2 journal in 2020-2022, there has not been much development in digitalization in maharah kitabah learning in the sinta 2 journal in 2020-2022. So it requires special attention for reputable journals sinta 2 to further increase the use of digital technology, especially in maharah kitabah learning.